Viva mesh Vegas [mesh wireless network]. - Cass, S.
In this paper, the mesh wireless network established by Cheetah Wireless Technologies Inc. is discussed. Cheetah's mobile wireless network is one of the first municipal installations to use mesh wireless technology, which allows users to access the Internet anywhere within the coverage area even if they're driving at 100 kph. Mesh networks have several key advantages over traditional wireless solutions, such as Wi-Fi or cellphones. Benefits include higher speeds, less susceptibility to radio interference, and greater resistance to network congestion. These networks also offer better coverage, the ability to prioritize different types of users, geolocation capabilities, tighter security, faster deployment, and a degree of immunity to catastrophic network failures.
Keywords: Internet; Wi-Fi.; Geolocation capability; Mesh wireless network; Mobile wireless network; Network congestion; Radio interference